Politische Kultur im neuen Staat: Eine Kritik der aktuellen Forschung - Herz, Thomas (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1993)
Ideas developed in a research project concerned with todays’ conflicts about the Nazi-past are applied to the present political culture in Germany and its interpretation by mainstream political culture research. This type of research is criticized because of it’s conservative bias.